2021
DOI: 10.1016/j.jcv.2021.104790
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sample pooling for SARS-CoV-2 RNA detection in nasopharyngeal swabs and salivas on the Roche Cobas 6800

Abstract: The Roche Cobas SARS-CoV-2 test recently received an Emergency Use Authorization from the U.S. Food and Drug Administration UA for pooling of up to six nasopharyngeal swab samples (NPS). We evaluated the 6-pool approach on both NPS and saliva samples using 564 samples (20 positive NPS and saliva samples each and 262 negative NPS and saliva samples each). The sensitivity of the Roche SARS-CoV-2 RNA test for pooled NPS samples was 100% (95%CI: 83.2-100%) and the sensitivity for pooled saliva samples was 90% (95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Respiratory specimens are not homogeneous in quality and the amount collected, and there are differences between reagents used, leading to large fluctuations in Ct values. In external quality programs of COVID-19 molecular tests conducted in Korea and other countries, a very wide range of Ct values (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) has been observed [44][45][46][47]. Making clinical judgments, e.g., on quarantine release, based on Ct values has a high probability of error [42,43,48,49].…”
Section: Results Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory specimens are not homogeneous in quality and the amount collected, and there are differences between reagents used, leading to large fluctuations in Ct values. In external quality programs of COVID-19 molecular tests conducted in Korea and other countries, a very wide range of Ct values (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) has been observed [44][45][46][47]. Making clinical judgments, e.g., on quarantine release, based on Ct values has a high probability of error [42,43,48,49].…”
Section: Results Reportingmentioning
confidence: 99%
“…However, recent prospective studies have revealed that the test sensitivities for saliva and ANS in asymptomatic patients were significantly lower than those for nasopharyngeal swabs [ 15 - 19 ]. In addition, pooled tests using saliva or ANS have lower sensitivities than individual tests using saliva or ANS [ 20 - 23 ]. Therefore, collecting such specimens can be considered for patients who need repeated specimen collection or in whom nasopharyngeal swabs are difficult to collect.…”
Section: Molecular Testsmentioning
confidence: 99%
“…The electronic search yielded 1907 entries, of which 1817 publications were removed for having no correlation to SARS-CoV-2 saliva-based test, absence of comparators, and for study duplicity, resulting in 90 publications being eligible for full-text review. Of these, 44 studies ( Azzi et al., 2020 ; Wong et al., 2020 ; Griesemer et al., 2021 ; Iwasaki et al., 2020 ; Kojima et al., 2020 ; Leung et al., 2021 ; McCormick-Baw et al., 2020 ; Pasomsub et al., 2021 ; Wyllie et al., 2020 ; Williams et al., 2020 ; Barat et al., 2021 ; McMillen et al., 2021 ; Nacher et al., 2021 ; Migueres et al., 2020 ; Otto et al., 2021 ; Hanson et al., 2020 ; Rao et al., 2021 ; Byrne et al., 2020 ; Skolimowska et al., 2020 ; Dogan et al., 2021 ; Landry et al., 2020 ; SoRelle et al., 2020 ; Jamal et al., 2021 ; Bhattacharya et al., 2021 ; Rutgers, 2020 ; Hitzenbichler et al., 2021 ; Aita et al., 2020 ; Babady et al., 2021 ; Braz-Silva et al., 2020 ; Chen et al., 2020 ; Güçlü et al., 2020 ; Hasanoglu et al., 2021 ; Kandel et al., 2020 ; Kim et al., 2020 ; Lai et al., 2020 ; Li et al., 2020 ; Lin et al., 2020 ; Moreno-Contreras et al., 2020 ; Perchetti et al., 2020 ; Procop et al., 2020 ; Senok et al., 2020 ; Sohn et al., 2020 ; Vaz et al., 2020 ; Yokota et al., 2021 ) met the eligibility criteria and were included in the study, whereas 46 articles were removed for not using PCR assay and the absence of NPS as a specific a comparator ( Table 2 ). All selected studies comprised studies on the basis of clinical surveys among patients with confirmed SARS-CoV-2 infection in the United States, the United Kingdom, Chi...…”
Section: Resultsmentioning
confidence: 99%